2017
DOI: 10.1017/s1751731117000039
|View full text |Cite|
|
Sign up to set email alerts
|

Growth of total fat and lean and of primal cuts is affected by the sex type

Abstract: Knowledge of tissue and cuts growth depending on the sex could be used to improve performance and efficiency. Computed tomography (CT) is a non-invasive technology that enables the study of the body composition of live animals during growth. The aims of the present study were (1) to evaluate variation in the body composition of four sex types (SEX) of pigs (castrated males (CM), immunocastrated males (IM), entire males (EM) and females (FE)) at the live weight of 30, 70, 100 and 120 kg, assessed using CT; (2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 22 publications
(25 reference statements)
4
7
0
Order By: Relevance
“…Thus, it seems that the growth of these muscles, at higher weights, is higher in the present work, probably due to differences in the genotypes used. Moreover, the allometric coefficients for ham (0.89-0.95) and loin (0.97) muscle weight with respect to the live weight of the pig were close to one in agreement with previous works that reported allometric coefficients between 0.87 and 1.13 for ham muscle and 1.01 and 1.03 for loin muscle (Carabús et al, 2014, Carabús et al, 2017.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, it seems that the growth of these muscles, at higher weights, is higher in the present work, probably due to differences in the genotypes used. Moreover, the allometric coefficients for ham (0.89-0.95) and loin (0.97) muscle weight with respect to the live weight of the pig were close to one in agreement with previous works that reported allometric coefficients between 0.87 and 1.13 for ham muscle and 1.01 and 1.03 for loin muscle (Carabús et al, 2014, Carabús et al, 2017.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, boars greater G:F might be explained by their greater growth potential and considering that there was no evidence of differences in ADFI ( O’Connell et al, 2006 ; Cámara et al, 2014 ). Moreover, in agreement with the literature, boars were generally leaner than gilts ( Cámara et al, 2014 ; Carabús et al, 2017 ) and had a reduced carcass yield, which might be partly attributed to the removal of the testicles ( Gispert et al, 2010 ). The differences in BFT were in agreement with Rikard-Bell et al (2013b) .…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with the literature, this study observed that boars have a greater ADG and G:F than gilts and a similar ADFI. The greater ADG of boars has been related to a higher potential for lean tissue deposition ( Hendriks and Moughan, 1993 ; Rikard-Bell et al, 2013b ), starting around 50 to 70 kg BW ( Whittemore et al, 1988 ; Giles et al, 2009 ; Carabús et al, 2017 ). Studies analyzing growth data have observed that gilts’ ADG compared with boars’ ADG starts to decline around 40 to 70 kg BW ( Campbell et al, 1988 ; Quiniou et al, 2010 ; Cámara et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Quality of pig carcasses, i.e. the presence of muscle and fatty tissue, depends on the sex (Renaudeau et al, 2005;Renaudeau and Mourot, 2007;Serrano et al, 2007;Radović et al, 2008, Carabús et al, 2017, which was also found in our studies of fat thickness, yield and meat share. According to Wagner et al (1999), male and female animals had almost the same share of fat tissue with 25 kg (6.92 and 7.00%), but with 100 kg it was higher in boars (16.33%) than in gilts (13.92 %).…”
Section: Methodssupporting
confidence: 83%